The Effect Of Knowledge And Experience Of Community Care On Interest In Treatment Moderated By Socioeconomics : (Study on Patients of Kefamenanu Hospital, TTU Regency) - Astrid, Mariana; Gunardi, Wani Devita; Wahyoedi, Soegeng (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2025)
RSUD Kefamenanu is one of the hospitals owned by the Regional Government of North Central Timor Regency which borders directly with the State of Timor Leste. RSUD Kefamenanu is the main referral for health services in North Central Timor Regency. The objectives of this study were (1) to analyze the effect of knowledge on interest in treatment at Kefamenanu Regional Hospital, North Central Timor Regency (2) to analyze the effect of previous treatment experience on interest in treatment at Kefamenanu Regional Hospital, North Central Timor Regency (3) to analyze whether socioeconomics moderates the effect of knowledge on interest in treatment at Kefamenanu Regional Hospital, North Central Timor Regency (4) to analyze whether socioeconomics moderates previous treatment experience on interest in treatment at Kefamenanu Regional Hospital, North Central Timor Regency. This research was conducted with a quantitative approach using a cross-sectional study design. This research was conducted at Kefamenanu Hospital, North Central Timor Regency. The population in this study were all patients of Kefamenanu Hospital, North Central Timor Regency with a sample size of 100 people. The analysis method used is moderation regression analysis. The results of the analysis show that (1) There is a positive relationship between service knowledge and interest in seeking treatment at Kefamenanu Hospital, This means that the better the patient's service knowledge, the higher the level of interest in seeking treatment at Kefamenanu Regional Hospital (2) There is a positive direct relationship between interest in seeking treatment at Kefamenanu Regional Hospital, meaning that the higher the patient's perception of previous treatment experience, the higher the level of interest in seeking treatment at Kefamenanu Regional Hospital (3) Socioeconomics partially moderates the effect of knowledge on interest in seeking treatment at Kefamenanu Regional Hospital, North Central Timor Regency (4) Socioeconomics partially moderates previous treatment experience on interest in seeking treatment at Kefamenanu Regional Hospital, North Central Timor Regency.